Molecular characterisation of carbapenem-resistant Pseudomonas aeruginosa clinical isolates in Nepal - Takahashi, Toshihiro; Tada, Tatsuya; Shrestha, Shovita; Hishinuma, Tomomi; Sherchan, Jatan B.; Tohya, Mari; Kirikae, Teruo; Sherchand, Jeevan B. (Journal of Global Antimicrobial Resistance, 2021)
•Molecular epidemiological analysis of 43 carbapenem-resistant Pseudomonas aeruginosa isolates from two hospitals in Nepal.•The P. aeruginosa isolates produced carbapenemases, including IMP-1, IMP-26, KPC-2, NDM-1, VIM-2 and VIM-5.•The P. aeruginosa isolates produced 16S rRNA methylases, including RmtB4 and RmtF2.•High-risk clones of P. aeruginosa, including ST235, ST244, ST357 and ST654, have emerged in hospitals in Nepal. The emergence of carbapenem-resistant Pseudomonas aeruginosa has become a serious worldwide medical problem. The aim of this study was to determine the genetic and epidemiological properties of carbapenem-resistant P. aeruginosa strains isolated from hospitals in Nepal. A total of 43 carbapenem-resistant P. aeruginosa isolates obtained from patients in two hospitals in Nepal between 2018 and 2020 were analysed. Their whole genomes were sequenced by next-generation sequencing. A phylogenetic tree was constructed from single nucleotide polymorphism (SNP) concatemers. Multilocus sequence typing (MLST) was performed and antimicrobial resistance genes were identified. Of the 43 isolates, 17 harboured genes encoding carbapenemases, including IMP-1, IMP-26, KPC-2, NDM-1, VIM-2 and VIM-5, and 12 harboured genes encoding 16S rRNA methylases, including RmtB4 and RmtF2. The carbapenem-resistant P. aeruginosa isolated in Nepal belonged to various sequence types (STs), including ST235 (5 isolates), ST244 (7 isolates), ST274 (1 isolate), ST357 (10 isolates), ST654 (3 isolates), ST664 (1 isolate), ST773 (1 isolate), ST823 (3 isolates), ST1047 (8 isolates), ST1203 (2 isolates) and ST3453 (2 isolates). To the best of our knowledge, this is the first molecular epidemiological analysis of carbapenem-resistant P. aeruginosa clinical isolates from Nepal. The findings strongly suggest that P. aeruginosa isolates producing carbapenemases and 16S rRNA methylases have spread throughout medical settings in Nepal.